2019
DOI: 10.1515/hf-2018-0208
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent viscoelastic properties of Chinese fir (Cunninghamia lanceolata) under hygrothermal conditions. Part 1: moisture adsorption

Abstract: To elucidate the frequency-dependent viscoelasticity of wood under a moisture non-equilibrium state, changes in stiffness and damping as a function of frequency were investigated during the moisture adsorption process. The moisture adsorption processes were carried out at six temperatures (30–80°C) and three relative humidity levels (30, 60 and 90% RH). During the moisture adsorption process, the wood stiffness decreased, and damping increased with the increment of moisture content (MC). Regardless of the mois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…The found scaling of horizontal shift factors a T with T g /T is also in line with various studies on time-temperature-moisture superposition (Fabre et al, 2018;Ishisaka et al, 2004;Krauklis et al, 2019;Patankar et al, 2008;Zhan et al, 2019;Zhang et al, 2020). This superposition is found for materials, where hydrogen bonding is important, such as wood, polyelectrolytes, polyamides, and epoxies.…”
Section: Discussionsupporting
confidence: 89%
“…The found scaling of horizontal shift factors a T with T g /T is also in line with various studies on time-temperature-moisture superposition (Fabre et al, 2018;Ishisaka et al, 2004;Krauklis et al, 2019;Patankar et al, 2008;Zhan et al, 2019;Zhang et al, 2020). This superposition is found for materials, where hydrogen bonding is important, such as wood, polyelectrolytes, polyamides, and epoxies.…”
Section: Discussionsupporting
confidence: 89%
“…However, the difference between 4 MPa and 7 MPa did not exceed 1%. At this stage, the BBS was subjected to a substantial external force, the bamboo cell walls were easily crushed, and the bundles were brittle, negatively impacting the physical properties of the bamboo scrimber [39,51]. ANOVA results indicated that the hot-press pressure exhibited a highly significant effect on the expansion rate of the water absorption thickness of bamboo scrimber (Table 4).…”
Section: Effect Of Hot-pressing Pressure On the Bbs Temperature And V...mentioning
confidence: 99%
“…A numerical simulation of creep behaviors have to be known. Numerous investigations have been conducted by considering the MS characteristics of wood and wood composites [3,[7][8][9][10][11][12][13]. However, only few MS properties were observed for a given property-MC combination.…”
Section: Introductionmentioning
confidence: 99%